Expression of human b-defensin-3 in oral squamous cell carcinoma using tissue microarray - A preliminary study - Hussaini, H.M.; Lim, P.K.; Rahman, R.A.; Abraham, T.; Cheong, C.S.; Zain, R.B.; Ismail, M.S.; Nam, A.N. (Wiley, 2006)
Purpose: Human b-Defensin (hBDs) is an epithelial origin, cationic antimicrobial peptides. Their expression is reported in oral mucosa, gingiva and salivary glands. However, their protective role is not well understood. It has been suggested that bacterial and viral infection are an important factors in the process of carcinogenesis. This study investigated the expression of hBD-3 in oral squamous cells carcinoma (OSCC). Methods: 29 OSCC and 23 samples of normal and dysplastic tissues were obtained from Oral Pathology diagnostic laboratory, faculty of Dentistry, UKM and UM. The tissues were arrayed and the expression of hBD-3 was analysed using immunohistochemistry technique. Results: Higher levels of hBD-3 expression were found in stage II and II of OSCC compared to stage I and IV. Expression of hBD-3 was also seen higher in the tumour front arrays. Healthy and dysplastic tissues also seen to expressed hBD-3 but most are moderately stained. Conclusion: High levels of hBD-3 expression is seen especially in stage II and III as well as in tumour front suggest a potential tumour marker, correlation between level of expression and probable infective cancer causes need to be investigate further.